Are discourse traditions individual or historical entities? The place of DTs in Eugenio Coseriu’s tripartition of language - López Serena, Araceli (Boletín de Filología, 2023)
This paper addresses the lack of consensus within the field of discourse traditions (DTs) −and more precisely regarding the Coserian tripartition of language into universal, historical, and individual levels− which results from Peter Koch’s understanding of DTs as entities meant to be embedded in the historical level, as opposed to that of Johannes Kabatek or Franz Lebsanft, according to whom they must be placed at the individual level. The specific aim sought is to show the criteria on which the scheme constructed by Coseriu relies by interweaving his tripartition of levels with the AristotelianHumboldtian one −in turn structured around the concepts of energeia, dynamis and ergon. The article thus reveals that the extent to which Koch’s position differs from Coseriu’s original proposal −to which Kabatek and Lebsanft remain faithful− can be explained in terms of how the opposition between the subject and the object of study and the ontology of the former is conceived in each case. Added to the above, this article likewise highlights the close link tying epistemology to ontology which becomes evident when closely examining the foundations that underpin the well-known Coserian tripartition.